2010
DOI: 10.1038/oby.2009.232
|View full text |Cite
|
Sign up to set email alerts
|

Combined Impact of Adiponectin and Retinol‐binding Protein 4 on Metabolic Syndrome in Elderly People: The Korean Longitudinal Study on Health and Aging

Abstract: The prevalence of metabolic syndrome (MS) increases with progressing and is potentially associated with changes in adipose‐derived cytokines, including adiponectin and retinol‐binding protein 4 (RBP4). We aimed to determine the prevalence of MS, and the relationships between these factors and MS in elderly people. A population‐based cohort study, the Korean Longitudinal Study on Health and Aging (KLoSHA), was performed on subjects aged ≥65 years by random stratified sampling in 2005–2006 (439 men and 561 women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 28 publications
2
36
0
Order By: Relevance
“…It was also considered a promising adipokine in humans possibly linking adiposity, insulin resistance, T2D, and certain components of the metabolic syndrome (32,33,35,47,48,(51)(52)(53)(54). However, in several clinical studies, associations and/or causality of observed RBP4 expression changes with these states could not be shown (9-11, 35, 71, 72, 93).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also considered a promising adipokine in humans possibly linking adiposity, insulin resistance, T2D, and certain components of the metabolic syndrome (32,33,35,47,48,(51)(52)(53)(54). However, in several clinical studies, associations and/or causality of observed RBP4 expression changes with these states could not be shown (9-11, 35, 71, 72, 93).…”
Section: Resultsmentioning
confidence: 99%
“…Circulating RBP4 levels also correlate with other components of the metabolic syndrome (32,(51)(52)(53)(54). It is suggested that RBP4 is a predictor of atherosclerosis and its clinical manifestations -cardiovascular diseases.…”
Section: Rbp4 In Insulin Resistance and T2d: Clinical Studiesmentioning
confidence: 99%
“…We previously demonstrated that increased prevalence of metabolic syndrome has been associated with low adiponectin levels even in relatively lean populations [34].…”
Section: Association Of Low Adiponectin Levels With Cardiometabolic Dmentioning
confidence: 99%
“…The total population of Seongnam was 977,166 in 2004 and the proportion of people aged 65 years or older was 6.2% [10]. One thousand subjects who were free from chest pain were selected using age-and sex-stratified random sampling from a roster of people aged 65 years or older in 2006.…”
Section: Study Populationmentioning
confidence: 99%
“…One thousand subjects who were free from chest pain were selected using age-and sex-stratified random sampling from a roster of people aged 65 years or older in 2006. Detailed information about recruitment was previously described [10]. In all, 439 men and 561 women were enrolled in the baseline cohort of KLoSHA.…”
Section: Study Populationmentioning
confidence: 99%